(untitled) (Sebha University Conference Proceedings, 2025)
Technological and industrial development as well as population growth have greatly increased the world’s demand for electricity. The latter is an important factor for national development. In fact, a large part of the world’s energy production, ensured by fossil sources, has led to global warming and increased pollution and depletion of conventional natural resources. Accordingly, the use of renewable energies, especially photovoltaics, has become a necessity to boost the production rate of electricity from non-fossil, sustainable and non-polluting resources. To that end, research center’s main emphasis has moved towards working on the optimization of photovoltaic systems. The present work aims to expose the potential of solar energy in Algeria. A presentation of the national program of renewable energy and energy efficiency of Algeria, consolidated by a thorough case study of a real PV power plant in Algeria is offered, which exposed a considerable deficit in achieving the desired objectives caused by both economic and health crisis in the entire world in recent years. The increase in this power plant power was chosen as an objective. Therefore, the effectiveness of the proposed solution could be determined based on sizing simulations, using PVSyst software, after the extension of the power plant.